Perhitungan penyusutan aset tetap berdasarkan SAK ETAP dan UU perpajakan dan implikasinya terhadap SHU Koperasi Karyawan PT. LEN Industri (Persero) - Destyan, Gema Dwiprakasa; Purbo, Giyanto; Sugito Putra, Toufiq Agung Pratomo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The difference in the calculation of depreciation of fixed assets based on SAK ETAP and the Taxation Law occurs because there are differences in the provisions for determining the acquisition price, useful life, depreciation method, and grouping types of fixed assets based on SAK-ETAP and the Taxation Law. This difference will affect the amount of SHU that will be received. The purpose of this study is to provide an overview of the differences in the calculation of depreciation of fixed assets based on SAK ETAP and the Taxation Law. The results of the calculation of the depreciation of fixed assets in 2016–2019 show differences in the total amount of depreciation and SHU before and after-tax where the calculation of depreciation of fixed assets based on SAK-ETAP shows an amount that is greater than the total calculation of depreciation of fixed assets based on the Income Tax Law. In addition, based on SAK-ETAP and the Taxation Law, the difference causes the amount of SHU before and after tax received by cooperatives under SAK-ETAP to be smaller than the amount of SHU before and after tax under the Taxation Law.